Pengaruh waktu fermentasi menggunakan ekstrak daun pepaya gantung terhadap kadar kafein kopi liberika - Fahimatul Ulya; Ahmad Soim Bahrul Ghufron (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
This research aimed to analyze the effect of fermentation time using hanging papaya leaf extract (Carica papaya var. pendens) as a source of papain enzyme on caffeine content and organoleptic properties of Liberica coffee (Coffea liberica). Papaya leaf extract with 80% concentration was applied to Liberica coffee beans with fermentation time variations of 24, 36, and 48 hours. Caffeine content analysis was performed using UV-Vis spectrophotometry at a wavelength of 273 nm. The results showed that fermentation duration significantly affected caffeine reduction. At 24 hours fermentation, the caffeine content of the treated sample (1.374 ppm) was relatively similar to control (1.357 ppm). The 36-hour fermentation showed a decrease in caffeine in the treated sample to 1.225 ppm compared to control (1.281 ppm), while the most significant reduction occurred at 48 hours fermentation with caffeine content of 1.145 ppm in the treated sample compared to 1.530 ppm in control (25.16% reduction). The mechanism of caffeine reduction involves the proteolytic activity of papain enzyme which hydrolyzes the protein-caffeine complex and modifies the permeability of coffee bean cell membranes. This research provides a foundation for the development of an enzyme-based natural decaffeination method for Liberica coffee, although further optimization is needed to meet commercial decaffeinated product standards.